Influencia de los tratamientos químicos de mercerizado, trimetoxisilanos y anhídrido maleico, sobre la estabilidad térmica de las fibras de lino - Ortiz Toledo, Cristian Orlando (2019)
The present investigation has like title "Influence of the mercerizados chemical treatments trimetoxisilanes and maleic anhydride, on the thermal stability of the linen fibers", with the main objective to evaluate the influence of the products: mercetizado, trimethoxysilanes and maleic anhydride, on the thermal fiber of flax. The line fibers were extracted manually. Fiber chemical treatments were carried out, such as mercerizing at 15% NaOH, 0.4% w / v silane and 5% maleic anhydride. After the treatments, the TGA analysis, the humidity and the chemical composition of the flax fibers were carried out. In the case of humidity, a maximum percentage of 11.77% and a minimum of 6.70% were obtained for the anhydride treatment respectively. Likewise, in the case of TGA, the moisture loss of the fibers without treatment of 9.89% and 6.93% for the fibers with maleic anhydride was evaluated in the range of 20 to 120 ° C. Finally, the fibers without treatment, mercerized, silane and anhydride have been found. Degradation temperatures of 347.5 ° C, 352.5 ° C, 336.5 ° C and 323.5 ° C respectively. Concluding that the treatment of maleic anhydride at 5%, in order to improve the thermal stability of the fibers, with a percentage by weight of 32% and the sample of fiber for the treatment, a 43.7% degradation was obtained. The analysis of ANAVA concludes that the independent variable in the field of flax fibers, and the percentage of degradation of flax fibers and their degradation temperature.